Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Waste paper-spent coffee grounds synergistically derived carbonized cellulose aerogel for multifunctional phase change materials: Enhancing thermal energy storage, Joule/solar heating, and electromagnetic shielding - Lihang Yang; Yutao Wang; Mingfeng Chen; Dehao Li; Feng Wang; Liyuan Zhang; Yu Liang; Renjie Chen; Jun Li (Biomass and Bioenergy, 2026)

Semaglutide treatment reverses HFD induced hippocampal microglia activation and improves cognitive dysfunction - Haodong Gong; Junlu Liu; Yihan Wang; Xufan Lin; Guangsen Wu; Yichao Ou; Mingfeng Zhou; le Yang; Junxiang Peng; Xinyun Ye; Yongjia Wang; Fei Xu; et al. (Tissue and Cell, 2026)

Physics-informed neural network for predicting reaction kinetics of quinoline hydrodenitrogenation - Shihao Wang; Tao Li; Yuelin Xu; Wenbin Chen; Xiaoqian Dang; Wei Zhang; Chen Zhang; Cuiqing Li; Yong Luo; Feng Liu; Mingfeng Li (Fuel, 2026)

Impact of microplastics and polycyclic aromatic hydrocarbons on microbial communities in marine sediments: A case study of the Bohai Sea - Jinfei Guo; Mingfeng Feng; Juntong Meng; Xinyu Liu; Xin Guan; Hailiang Song; Dai Jia; Zhicheng Xie (Environmental Pollution, 2026)

Intercropping enhances soil organic carbon accumulation by modulating microbial interactions in saline-alkali soils - Lijun Zhang; Guixiang Zhou; Jiabao Zhang; Lin Chen; Congzhi Zhang; Donghao Ma; Hui Zhang; Jian Feng; Mingfeng Liu (Applied Soil Ecology, 2026)

GNSS/MEMS INS tightly coupled algorithm for agricultural machinery navigation enhanced by random forest-based behavioral state awareness - Yihang Feng; Guanwen Huang; Mingfeng Wang; Xin Li; Zhenhong Li; Hang Li; Kai Zhang; Ce Jing (Computers and Electronics in Agriculture, 2026)

Insight into metal-support interactions of NiMo hydrodesulfurization catalysts and their variations during application - Wenhui He; Yanjuan Xiang; Mudi Xin; Weiming Zhai; Sicong Qiao; Nan Zhang; Limei Qiu; Siyang Yan; Feng Liu; Jianqiang Wang; Guangtong Xu; Jiaxu Liu; et al. (Chemical Engineering Journal, 2025)

Isolation and Identification of Metanophrys sinensis from Shrimps (Litopenaeus vannamei) and Screening of Chinese Herbal Medicines for Its Control - Mingfeng Ge; Yifan Xu; Juan Feng; Zheng Liang; Hao Cui; Xinxin Jiang; Jianping Wang; Shengwei Xu; Rongrong Ma (Fishes, 2025)
The parasitic disease scuticociliatosis poses significant economic losses to shrimp culture. In this study, an unidentified species of ciliates was discovered in Litopenaeus vannamei. Morphological and molecular analyses were conducted to identify the parasite species, while a reinfection experiment was performed to assess its virulence towards L. vannamei. Simultaneously, Chinese herbal medicine was assessed for potential prevention and control of this pathogen. The results revealed that the SSU rDNA (93.87%), LSU rDNA (98.20%), and ITS1-5.8S-ITS2 rDNA (87.10%) genes exhibited high homology with Metanophrys sinensis, suggesting its classification within the genus Metanophry sp. The reinfection experiment demonstrated median lethal dosages of 6638 individuals/mL at 24 h and 4658 individuals/mL at 48 h for this ciliate on the host L.vannamei. In terms of drug control, we conducted a screening of 23 Chinese herbal extracts through in vivo injection trials and observed that Mume fructus extract exhibits potent biocidal activity. Specifically, the M. fructus extract solution with a final concentration of 5 mg/mL (0.5% v/v) eliminated all ciliates within 3 h. In conclusion, this study identified the ciliate parasite as Metanophrys sinensis and demonstrated its virulence to Litopenaeus vannamei. Mume fructus extract was found to effectively control the parasite, offering potential for managing scuticociliatosis in shrimp culture.

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Influence of aromatics on the hydrodesulfurization reaction pathway of the NiMo/Al2O3 catalyst using quasi-in situ characterization techniques - Longxin Gao; Wenhui He; Weiming Zhai; Mudi Xin; Wei Wang; Yanjuan Xiang; Hui Yuan; Sa Wang; Feng Liu; Guangtong Xu; Limei Qiu; Mingfeng Li (Fuel, 2025)

IRBITs, signaling molecules of great functional diversity - Ying Liu; Xuhui Feng; Han Wu; Tianxiang Gui; Mingfeng Fu; Xudong Luo; Lei Zhao; Li-Ming Chen (Pflügers Archiv - European Journal of Physiology, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Promotion mechanism of rare-earth elements doping on performance of CaO/CeO2 sorbent for high temperature CO2 capture - Yunfeng Li; Jiarui Wu; Feng Liu; Weiwei Liu; Bin Li; Qingfa Zhang; Mingfeng Wang; Haiping Yang; Zhen Fang; Zhong Ma (Chemical Engineering Journal, 2025)

Genetic characterization of a novel HIV-1 circulating recombinant form (CRF162_cpx) involving CRF01_AE, CRF07_BC and subtype B in Guangdong, China - Yun Lan; Linghua Li; Mingfeng Xiao; Yaqing Lin; Xuemei Ling; Feng Li; Fengyu Hu (Virus Genes, 2025)

A leader-adaptive particle swarm optimization with dimensionality reduction strategy for feature selection - Shanshan Yang; Bo Wei; Li Deng; Xiao Jin; Mingfeng Jiang; Yanrong Huang; Feng Wang (Swarm and Evolutionary Computation, 2024)

In situ tracking of the impact of atomic-scale fragment structures on MoS2 nanocrystals for high-stability industrial NiMo/γ-Al2O3 hydrodesulfurization catalysts - Wenhui He; Mudi Xin; Yanjuan Xiang; Weiming Zhai; Zheng Chen; Limei Qiu; Aiguo Zheng; Feng Liu; Le Zhang; Guangtong Xu; Mingfeng Li (Chemical Engineering Journal, 2024)

Zero-valent iron (nZVI) nanoparticles mediate SlERF1 expression to enhance cadmium stress tolerance in tomato - Ali Anwar; Yudan Wang; Mengqing Chen; Shuaiwei Zhang; Jinmiao Wang; Yunqiang Feng; Yanxu Xue; Mingfeng Zhao; Wei Su; Riyuan Chen; Shiwei Song (Journal of Hazardous Materials, 2024)

Influence of large-scale climate indices and regional meteorological elements on drought characteristics in the Luanhe River Basin - Min Li; Zilong Feng; Mingfeng Zhang; Yuhang Yao (Atmospheric Research, 2024)

Effective reduction of hydrogen consumption in ultra-deep hydrodesulfurization of diesel: Deep insights into the effect of thermodynamic limitations during hydrotreating - Yubai Zhang; Feng Liu; Wenbin Chen; Wei Han; Weiming Zhai; Yutao Lu; Mingfeng Li (Fuel, 2024)

A novel approach to achieving more efficient production of the mature form of human IL-37 in plants - Yao Zhang; Nadiyah Alqazlan; Zihe Meng; Jingyao Zhao; Nan Liu; Yuxin Zhang; Mingfeng Feng; Shengwu Ma; Aoxue Wang (Transgenic Research, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

SERS “hot spot” enhance-array assay for misfolded SOD1 correlated with white matter lesions and aging - Feng Gao; Jingyi Sun; Minmin Yao; Yanan Song; Hui Yi; Mingfeng Yang; Qingbin Ni; Jiming Kong; Hui Yuan; Baoliang Sun; Ying Wang (Analytica Chimica Acta, 2023)

Carbonyl Reductase 1 Attenuates Ischemic Brain Injury by Reducing Oxidative Stress and Neuroinflammation - Leilei Mao; Kun Wang; Pengjie Zhang; Shihao Ren; Jingyi Sun; Mingfeng Yang; Feng Zhang; Baoliang Sun (Translational Stroke Research, 2021)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)